The relationship between harsh parenting, shyness and cyber victimization: based on the cross-lagged panel model and the random intercept cross-lagged panel model - Zhao, Xintong; Xin, Tao; Sang, Qingsong (Frontiers in Psychiatry, 2025)
ObjectiveTo examine the longitudinal associations between harsh parenting, shyness, and cyber victimization. The present study hypothesized that shyness mediated harsh parenting and cyber victimization.MethodsEight hundred and twenty-eight first-year middle school students voluntarily completed three rounds of questionnaires investigating harsh parenting, shyness, and cyber victimization at eight-month intervals. CLPM and RI-CLPM were conducted using SPSS 26.0 and Mplus 8.3.ResultsShyness was a significant predictor of cyber victimization and harsh parenting had a significant prospective effect on cyber victimization. Shyness mediated longitudinally between harsh parenting and cyber victimization.ConclusionsIn CLPM, T1 and T2 harsh parenting significantly and positively predicted T3 cyber victimization, with shyness serving as a mediator in the longitudinal relationship between harsh parenting and cyber victimization. In RI-CLPM, at the within-individual level, T1 harsh parenting significantly and positively predicted T2 cyber victimization, T2 shyness mediated the relationship between T1 harsh parenting and T3 cyber victimization. This study deepens our understanding of the dynamic relationship among harsh parenting, shyness, and cyber victimization, providing robust empirical evidence and meaningful insights for interventions in adolescent cyber victimization.